Human Resource Management Practices in the Philippines - Roman, Emerlinda R. (Philippine Management Review; Vol 7 (1997), 2016)
Seventy six human resource (HR) managers of public and private firms participated in a survey about human resource management (HRM) practices.  Two of the more notable findings of the study are:  1) although HR departments continue to be strongly involved in traditional, bureaucratic personnel management functions (recruitment, selection, record-keeping, etc.), there are indications of their increasing participation in strategic decision-making of their firms (development of HR strategies, initiation and implementation of strategic HR programs); and 2) HRM is increasingly recognized as somewhat of a profession with a body of specialized knowledge, a service objective, a code of ethics and an organized professional society or association.  The challenge facing HR managers is how to sustain efforts to develop HR departments into strategic partners playing a vital role in pursuing the firms’ strategic directions.